2015
DOI: 10.1542/peds.2015-1120
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Infant Pertussis Infection in the United States

Abstract: BACKGROUND: Pertussis is poorly controlled, with the highest rates of morbidity and mortality among infants. Although the source of infant pertussis is often unknown, when identified, mothers have historically been the most common reservoir of transmission. Despite high vaccination coverage, disease incidence has been increasing. We examined whether infant source of infection (SOI) has changed in the United States in light of the changing epidemiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 17 publications
7
64
0
12
Order By: Relevance
“…Additional information has emerged in a number of reports from Australia and The Netherlands indicating that older children have become the most common SOI to their infant brothers and sisters (253,524,542). In September 2015, Skoff and colleagues used enhanced pertussis surveillance data collected over an 8-year period (2006 to 2013) from seven states (Colorado, Connecticut, Massachusetts, Minnesota, Mexico, New York, and Oregon) to identify the most common source of pertussis infection in the United States (543). The results of this study showed that siblings (mean age, ϳ8 years) are the main SOI (35.5%), followed by mothers (20.6%), and fathers (10%).…”
Section: Tdap Immunization For Pregnant Womenmentioning
confidence: 99%
“…Additional information has emerged in a number of reports from Australia and The Netherlands indicating that older children have become the most common SOI to their infant brothers and sisters (253,524,542). In September 2015, Skoff and colleagues used enhanced pertussis surveillance data collected over an 8-year period (2006 to 2013) from seven states (Colorado, Connecticut, Massachusetts, Minnesota, Mexico, New York, and Oregon) to identify the most common source of pertussis infection in the United States (543). The results of this study showed that siblings (mean age, ϳ8 years) are the main SOI (35.5%), followed by mothers (20.6%), and fathers (10%).…”
Section: Tdap Immunization For Pregnant Womenmentioning
confidence: 99%
“…22,23 A recent study found that siblings (median age 8 years) are now the most common source of pertussis infection in infants 24 ; however, it is not clear whether adolescent Tdap boosters are important for protecting infants. 25 Tdap vaccination of pregnant women is likely to have a larger impact on pertussis in infants.…”
Section: Figurementioning
confidence: 99%
“…These findings were expected because pertussis is highly infectious and spreads easily within households and communities. The results from a 2015 investigation indicated that siblings are the primary source of pertussis infection among infants (52). Thus, communities where there are high levels of nonmedical vaccine exemptions have some risk for community-level pertussis outbreaks in both young children and adolescents.…”
Section: Nonmedical Vaccine Exemptionsmentioning
confidence: 99%